Dostoevsky and the ethics of narrative form: suspense, closure, minor characters - Matzner-Gore, Greta (Studies in Russian literature and theory, 2020)
Inhaltsverzeichnis: Introduction -- Curiosity, Suspense, and Dostoevsky's Demons -- The Endings of The Adolescent -- From the Corners of The Brothers Karamazov: Minor Characters in Dostoevsky's Last Novel -- Conclusion.